INTERPRETATION OF THE ARTISTIC AND SCIENTIFIC POTENTIAL OF THE TURKIC LANGUAGE IN THE WORKS OF ALISHER NAVOI (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the artistic and scientific potential of the Turkiclanguage as interpreted in the works of Alisher Navoi. It highlights Navoi’s decisive rolein the formation and development of the Uzbek literary language, particularly through histreatise “Muhokamatu-l-lugʼatayn,” in which he demonstrated the equality of Turkic withPersian. The study analyzes Navoi’s contribution to the evolution of Uzbek poetry andfocuses on the integration of Arabic and Persian lexical elements within the epic “SabʼaiSayyor” from his “Khamsa.” Using comparative-analytical and historical-linguisticmethods, the research explores semantic changes and stylistic functions of loanwords.The findings confirm that Navoi not only elevated the status of the Turkic language butalso created a new poetic model that harmonized different linguistic traditions, layinga strong foundation for the future development of Uzbek literature.
Keywords: Alisher Navoi; Uzbek literary language; Turkic language; Arabic loanwords; Persian influence; Sabʼai Sayyor; Khamsa; linguistic analysis; poetics; literary development.